The Effects of High-Performance Work Practices on Perceived Organizational Support and Turnover Intentions: Evidence from the Airline Industry - Karatepe, Osman M.; Vatankhah, Sanaz (My University, 2014)
The present study examines the simultaneous impacts of high-performance work practices on perceived organizational support and turnover intentions. Data were collected from flight attendants with a time lag of two weeks in Iran to assess these relationships. The results reveal that career opportunities, empowerment, selective staffing, rewards, job security, teamwork, and training as the indicators of high-performance work practices foster perceived organizational support and reduce turnover intentions. Management implications and avenues for future research are provided in the current study. © 2014 Copyright © Taylor & Francis Group, LLC.
Keywords: flight attendants; high-performance work practices; Iran; perceived organizational support; turnover intention